A mobile application for cognitive screening of dementia. Issue 2 (February 2015) - Zorluoglu, Gokhan; Kamasak, Mustafa E.; Tavacioglu, Leyla; Ozanar, Pinar O.
<x xml:space="preserve">Abstract</x> Highlights A novel mobile cognitive screening (MCS) test is designed for mobile devices. MCS has easier interface for elderly participants compared to the personal computers. MCS can offer a wider range of multimedia components compared to the paper tests. MCS can compare cognitive functions against the average of healthy individuals'. MCS can differentiate healthy and impaired cognitive abilities.